Effect of Mycorrhizal and Organic Fertilizer on the Growth of Garlic - Wicaksono, Muhammad Imam; Rahayu, Muji; Samanhudi, Samanhudi (Caraka Tani - Jurnal Ilmu Ilmu Pertanian, 2014)
Garlic has a high price in the market, however, production of garlic has its limitations. The use of chemical fertilizers has shortcomings in terms of environmental sustainability, soÂ  need for organic fertilizer which serves to reduce the negative impact. The study aims to determine interactive between kinds of mycorrhizal and organic fertilizer to garlic, get the appropriate mycorrhizal and to get the Suistainablekind of fertilizer to increase of the garlic yield. The experiment was conducted from January 2013 to August 2013. Research using CRD (completely randomized design) with 2 factors of organic fertilizer (chicken manure, cow manure, goat manure, manure and vermicompost compost) and mycorrhizal types (Gigaspora margarita, Acaulospora sp, Glomus etunicatum). The results showed mycorrhizal mycorrhizal types Gigaspora margarita is suitable and capable of enhancing the growth of garlic, application of organic fertilizers used have not been able to increase the growth and yield of garlic. Applications of various types of mycorrhiza and organic fertilizers have not been able to increase the growth of garlic.